Multidisciplinary nexus for global public health challenges - Aminul Haque; Siwi Pramatama Mars Wijayanti; Budi Aji (Public Health Department, Faculty of Health Sciences, Jenderal Soedirman University, 2020)
Disease pandemic has shown that human health does not belong to health human resources only but beyond it. People should realize that health issues could not only be relied on the health sector but it also needs a cross-cutting stakeholders such as social scientists, economists, politicians, non-governmental organizations, mass media, private entities, mass participation etc. So, human health belongs to the participation of everyone because it comes from everyone. No one will deny it!